Removal of lead from water using liquid-liquid extraction process - Chua, Siew Hwee (2023)
Lead is considered as a hazardous heavy metal due to its toxicity and ability to bring a variety of harmful impacts on both humans and the environment. Liquidliquid extraction is known as a powerful separation technology that is increasingly being employed in many chemical process industries to remove heavy metals from wastewater. However, the extensive usage of a large amount of hazardous conventional organic solvents in the liquid-liquid extraction process has significant drawbacks due to their relatively low volatility. Based on that, the greener ionic liquids have recently obtained essential attention as an alternative type of extractant to perform an effective extraction of lead from water through liquid-liquid extraction due to their excellent ionic characteristics. The study investigated the implementation of ionic liquids and organic extractants in the extraction of lead from water via a liquid-liquid extraction process. The study also examined various parameters that affect the removal of lead from water, in which including the effect of different types of extractants used, the impact of hydrochloric acid concentration in the aqueous phase, the initial lead concentration in water, and the volume-to-mass ratio between lead solution and extraction mixture. Based on the study findings, the highest removal efficiency of lead is achieved by Cyphos IL 101 (64.32%), which is followed by Trioctylamine (44.44%) and trihexyltetradecylphosphonium dicyanamide IL (37.97%). Additionally, the higher removal efficiency was achieved at higher HCl concentration for all extractants studied, as a result of the formation of quaternary ammonium cation, R3NH+ and lead tetrachloride, PbCl42- is required to promote a better extraction process for both complex formation and anionic exchange mechanism. Besides, the higher removal efficiency was attained at a higher initial lead concentration due to a higher concentration gradient between the aqueous phase and extractant phase were created. The performance of the extractants was also highly dependent on the volume-to-mass ratio between the lead solutions to extractant, where a lower removal efficiency was observed with the elevated volume-to-mass ratio as the extractants available within the extraction mixture is inadequate to accommodate the increased amount of lead ions in water.